Changes - Boyle, Bill; Boyle, Bill William; Heinemann Educational Books Ltd. (London Heinemann Educational Books Ltd, 1900)
This book uses a sequence of whimsical illustrations to show how one object can gradually change into another$1 (Bstimulating young readers$1 (Bsense of surprise and observational thinking. The text encourages readers to look for differences and similarities while building vocabulary and visual literacy.s
Published as part of the Reading 360 beginner-level reading program for developing early literacy and observation skills. Includes full-colour artwork and guided text to promote vocabulary acquisition.
b
Keywords: Picture books for children-Perception-Visual Discrimination-Change